Chapter 11 Vitamin C and the Brain - Hoffer, Leonard John (Taylor & Francis, 2020)
The brain requires vitamin C to metabolize fuel substrates and synthesize neurotransmitters, regulate their release, and modify their actions. Vitamin C also protects the brain from oxidative damage. Clinical studies do not provide strong evidence that vitamin C deficiency directly impairs brain function but rather suggest that the fatigue, mood disturbance, and cognitive dysfunction sometimes associated with vitamin C deficiency are due to peripheral tissue damage, with possibly an exaggerated emotional response to it. Severe brain injury drastically depletes the cerebrospinal fluid of vitamin C; clinical trials of high-dose intravenous vitamin C are strongly warranted for this condition. The very limited clinical trial evidence available does not demonstrate that vitamin C supplementation slows the progression of dementia or improves clinical outcomes after an acute ischemic stroke. Hypovitaminosis C is common in people with severe mental illness; it should be treated. A few clinical trials have been carried out of low-pharmacologic doses of vitamin C (alone or with other nutrients) as adjunctive therapy in patients with chronic stable schizophrenia or depression, with inconsistent results. There is plausible but inclusive evidence that continuous supplementation with a combination of several micronutrients, including vitamin C, may have cognitive benefits in some people even if they lack diagnosed vitamin deficiencies.